Administration of hyoscine- n-butylbromide during colonoscopy: a survey of current UK practice. Issue 4 (16th June 2012) - Bedford, Matthew Robert; Reuser, Tristan; Wilson, Paul; Karandikar, Sharad; Bowley, Douglas
Abstract : Objective: Current British Society of Gastroenterology (BSG) guidelines suggest that hyoscine-n-butylbromide (Buscopan) should be avoided during colonoscopy in patients with a history of angle-closure glaucoma. Angle-closure glaucoma, however, is not very common, is asymptomatic before onset and is treated definitively by a single laser treatment (if spotted early). Open-angle glaucoma is not affected by hyoscine . The aim of this study was to assess the use of hyoscine among colonoscopists, with particular reference to glaucoma. Design and setting: Following BSG endoscopy subcommittee approval, a short questionnaire was electronically administered to members of the BSG and the Association of Coloproctology of Great Britain and Ireland. Main outcome measures: Hyoscine use among colonoscopists, and effect of glaucoma history upon prescribing practice. Results: 188 colonoscopists responded to some or all of the questions. 123/183 (67.2%) of respondents claimed they were aware of the BSG guidelines. 160/187 (85.6%) sometimes or always use hyoscine, while 27/187 (14.4%) never do. 137/177 (77.4%) always enquire about glaucoma history prior to administration, although 147/176 (83.0%) make no differentiation between open-angle or angle-closure forms. 126/178 (70.8%) would (incorrectly) withhold hyoscine if the patient declares a history of any form of glaucoma. 140/179 (78.2%) do not substitute glucagon as an antispasmodic. 4/180 (2.2%) had encountered ophthalmic complications post-administration. Conclusions: Current BSG guidelines pertaining to hyoscine use and glaucoma are inappropriate; the authors recommend revision. Patients undergoing colonoscopy who have received hyoscine should, instead, be advised to seek urgent medical advice if they develop ophthalmic symptoms.